Chemistry and chemical technology. Lithuanian chemists conference, May 16, 2019 - Ramanavičienė, Almira; Inkrataitė, Greta; Daumantas, Liudas (Vilnius University Proceedings, 2019)
The aim of the conference is to bring together young scientists, engineers, researchers and students of Lithuanian universities, institutes, centers of science and business to carry out research in the field of chemistry and chemical technology, to provide the opportunity to expand knowledge and present the latest scientific results and ideas.